High risk electrocardiographic markers in Brugada syndrome. (March 2018) - Asvestas, Dimitrios; Tse, Gary; Baranchuk, Adrian; Bazoukis, George; Liu, Tong; Saplaouras, Athanasios; Korantzopoulos, Panagiotis; Goga, Christina; Efremidis, Michael; Sideris, Antonios; Letsas, Konstantinos P.
Abstract: Several clinical, electrocardiographic (ECG) and electrophysiological markers have been proposed to provide optimal risk stratification in patients with Brugada syndrome (BrS). Of the different markers, only a spontaneous type 1 ECG pattern has clearly shown a sufficiently high predictive value. This review article highlights specific ECG markers based on depolarization and/or repolarization that have been associated with an increased risk of arrhythmic events in patients with BrS.